2018
DOI: 10.31989/ffhd.v8i11.565
|View full text |Cite
|
Sign up to set email alerts
|

Furosap, a novel Fenugreek seed extract improves lean body mass and serum testosterone in a randomized, placebo-controlled, double-blind clinical investigation

Abstract: Background: The Indian spice fenugreek (Trigonella foenum-graecum) has been credited with numerous health benefits in cardiovascular disorders, metabolic syndrome, inflammatory conditions, glucose-insulin regulation, and sports performance. Previous studies from our laboratories demonstrated that fenugreek seed extract improved glucose tolerance, insulin sensitivity, augmented serum testosterone level and improved cardiovascular functions. Our investigation examined the efficacy of Furosap, a novel fenugreek s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…In support of the findings of this review, a recent meta-analysis of clinical trials on fenugreek seed extract supplementation reported a significant increase in testosterone concentrations (68). This meta-analysis included 4 studies (42,58,63,64) but did not include 2 of the studies included in this review because it was conducted in late 2018 and excluded studies with a duration <4 wk. Similar to the findings of the current review, Qureshi et al (69) conducted a systematic review on all tribulus studies examining various forms of testosterone in animals and humans and concluded that the evidence indicated that it is ineffective at increasing testosterone concentrations in humans.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…In support of the findings of this review, a recent meta-analysis of clinical trials on fenugreek seed extract supplementation reported a significant increase in testosterone concentrations (68). This meta-analysis included 4 studies (42,58,63,64) but did not include 2 of the studies included in this review because it was conducted in late 2018 and excluded studies with a duration <4 wk. Similar to the findings of the current review, Qureshi et al (69) conducted a systematic review on all tribulus studies examining various forms of testosterone in animals and humans and concluded that the evidence indicated that it is ineffective at increasing testosterone concentrations in humans.…”
Section: Discussionmentioning
confidence: 53%
“…Six studies (42,53,57,58,63,64) were conducted examining the effects of fenugreek seed extracts on testosterone concentrations. Three studies used the Testofen® extract, manufactured by Gencor TM (also known as Fenu-FG) (details of extract preparation not provided) (57,58,63) and the other 3 studies used the extracts IND9, manufactured by Indus Biotech® (53), Furosap®, manufactured by Chemical Resources (CHERESO) (42), and an extract standardized for Grecunin, manufactured by Indus Biotech® (64) (details of all extract preparations not provided). Five studies were randomized, double-blind, placebo-controlled trials (42,57,58,63,64) and one was a randomized, double-blind, placebo-controlled crossover study (53).…”
Section: Trigonella Foenum-graecum (Fenugreek)mentioning
confidence: 99%
See 3 more Smart Citations